Peran Preoccupied Attachment Style terhadap Kecenderungan Mengalami Stockholm Syndrome pada Perempuan Dewasa Awal - Arlin Yuliani; Nurindah Fitria (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2017)
Good romantic relationship occurs when a couple can solve their conflict in an effective way. Unfortunately, not all couples can do it, on the top of that the conflict become a violence. Eventhough the victim has been hurted many times, they still cannot leave violent relationship because of emotional bond between the victim and the perpretator, which is called as stockholm syndrome. One factor which can affect this condition is attachment style, especially insecure attachment style, such as preoccupied attachment style. Insecure attachment style can make the victim stuck with relationship which full of violence. The aim of this research was to analyze the role of preoccupied attachment style towards the tendency to experience stockholm syndrome in young adulthood women. This research used quantitative approach. 323 participants were selected using accidental sampling technique. The measurements were the preoccupied dimension from the Attachment Styles Questionnaire and the Stockholm Syndrome Scale. Regression testing showed that preoccupied attachment style had a significant role towards the tendency to experience stockholm syndrome (1.9%).